2006
DOI: 10.1002/j.1556-6678.2006.tb00430.x
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Future: A Study of Resilience in Suicidal Female Adolescents

Abstract: The authors designed this study to understand how adolescents overcome suicidality from the subjective perspective of 13 previously suicidal female participants. A resilience framework was used to conceptualize the process. Data analysis using basic interpretive qualitative inquiry revealed 4 domains of resilience: social processes, emotional processes, cognitive processes, and purposeful action. The domains were inextricably linked; improvements in 1 domain produced changes across others, adding momentum to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
90
1
24

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(125 citation statements)
references
References 33 publications
10
90
1
24
Order By: Relevance
“…The association between greater perceived friendship quality and increased resilience revealed in this study supports previous qualitative evidence that close, supportive friendships facilitate resilience processes (Everall, Altrows & Paulson, 2006;Shepherd, Reynolds & Moran, 2010). A single close, or relatively close, friendship is available to most adolescents regardless of social competence, extraversion or closeness preferences (Finkenauer & Righetti, 2011).…”
Section: Association Between Close Friendship Support and Resiliencesupporting
confidence: 86%
“…The association between greater perceived friendship quality and increased resilience revealed in this study supports previous qualitative evidence that close, supportive friendships facilitate resilience processes (Everall, Altrows & Paulson, 2006;Shepherd, Reynolds & Moran, 2010). A single close, or relatively close, friendship is available to most adolescents regardless of social competence, extraversion or closeness preferences (Finkenauer & Righetti, 2011).…”
Section: Association Between Close Friendship Support and Resiliencesupporting
confidence: 86%
“…The significant role of social support has been well documented in research. Specifically, Everall et al (2006) found that Caucasian adolescents in who had at least one significant supportive relationship with an individual (i.e., mother, caregiver, or teacher) had less suicidal ideation, compared to participants who lacked a supportive significant relationship. Similarly, found that having a close significant relationship with a parental figure, family member, or mentor was a contributing factor for adolescents who demonstrated resilience.…”
Section: Predictors Of Resiliencementioning
confidence: 99%
“…However, some researchers have explored resilience among different groups of adolescents. Specifically, Everall, Altrows, and Paulson (2006) qualitatively investigated resilience among a group of female Caucasian adolescents that overcame suicidal ideation. The researchers were primarily interested in understanding how these adolescents perceived overcoming suicidal ideations.…”
Section:  mentioning
confidence: 99%
See 1 more Smart Citation
“…Everall, Altrows and Paulson (2006) determined that resilience research has predominantly focused on one of three operational definitions: (a) a stable personality trait or ability protecting individuals from negative effects of risk and adversity (i.e., Dumont & Provost, 1999;Werner, 1995); (b) a positive outcome, which is defined by the presence of positive mental health or absence of psychopathology, despite the exposure to risk (Masten & Powell, 2003); or (c) a dynamic process that is dependent upon interactions between individual and contextual variables, and which evolves over time. The third perception of resilience is that of a "dynamic developmental process reflecting evidence of positive adaptation despite significant life adversity" (Luthar, 2003, p. xix).…”
Section: Review Of Literaturementioning
confidence: 99%